2018
DOI: 10.3390/antibiotics7040108
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Hypokalemia Possibly Induced by Nafcillin

Abstract: (1) Background: The use of intravenous antibiotics for severe infections is a common practice, either as inpatient or outpatient treatment. In the case of methicillin-susceptible Staphylococcus aureus (MSSA), nafcillin is a commonly prescribed intravenous antibiotic, given its known efficacy to treat infections related to this organism effectively. However, it is not without side effects. (2) Methods: We present an interesting case of persistent hypokalemia in a patient after he was started on nafcillin infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is known that the metabolic byproducts of some antibiotics, such as tetracyclines, accumulate inside the mitochondria of renal cells and prevent oxidative phosphorylation, leading to metabolic acidosis [ 29 ]. Acidosis is often concomitant with reduced plasma calcium and chloride levels [ 30 ]. The histopathological observations of the current study further confirmed the cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the metabolic byproducts of some antibiotics, such as tetracyclines, accumulate inside the mitochondria of renal cells and prevent oxidative phosphorylation, leading to metabolic acidosis [ 29 ]. Acidosis is often concomitant with reduced plasma calcium and chloride levels [ 30 ]. The histopathological observations of the current study further confirmed the cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of hypokalemia include muscle weakness, cramping, fatigue, and constipation. Severe hypokalemia can be life-threatening, leading to muscle paralysis, respiratory failure, or heart arrhythmias [ 69 ].…”
Section: Essential Metals In Foodmentioning
confidence: 99%
“…Several mechanisms have been associated with amphotericin B-induced electrolyte disturbances such as changes in the Na+-K+-ATPase pump in the distal tubule, and increased absorption of Na+ in the gastrointestinal tract, with resultant excretion of K+ in the feces. 3,15…”
Section: Renal Lossmentioning
confidence: 99%